Public perception of artificial intelligence in leadership : trust, skills, and desirability - Dorner, Felix-Constantin (2024)
Topic: The integration of Artificial Intelligence (AI), particularly Generative AI, is transforming business processes and prompting questions about its potential role in leadership. This thesis investigates public perceptions of AI leadership in comparison to human leadership, focusing on key trust factors (ability, integrity, and benevolence) and the perceived competence of AI in essential leadership skills, and how these factors impact the desirability of AI in a leadership role. Methods: Two quantitative studies were conducted. Study 1 examined trust in AI leadership in direct comparison to trust in human leadership. Study 2 assessed public perceptions of AI9s capabilities in fulfilling leadership roles based on the 23 essential leadership skills identified in the O*NET Database. The studies are based on randomized samples from 314 participants (Study 1) and 207 participants (Study 2). Findings: Results from Study 1 revealed that human leaders are significantly more desired than AI leaders, driven by differences in perceived trustworthiness, (ability, integrity, and benevolence), whereas ability was the strongest factor. Study 2 showed that while AI is perceived as capable in technical skills, its lack of social skills, particularly negotiation and social perceptiveness, negatively affects its overall desirability and perceived capability as a leader. The results show that a decrease in perceived ability (trust factor) does lead to a significant decrease in trust, whereas an increase in perceived skill level does not lead to an increase in desirability. The findings highlight the need for AI to improve its social capabilities to be accepted in leadership roles.